Shot clock - Butler, Caron, 1980-; Reynolds, Justin A. (Butler, Caron, 1980- Shot clock novel, 2022)
After the death of his friend, Tony must work to make the basketball team, but when he gets the chance to join the squad as statistician, he must grapple with honoring the memory of his basketball-loving friend while also trying to fit in on the team.